Direct measurements, numerical predictions and simple formula estimations of welding-induced biaxial residual stresses in a full-scale steel stiffened plate structure. (February 2021) - Yi, Myung Su; Noh, Sung Hwan; Lee, Dong Hun; Seo, Dong Houi; Paik, Jeom Kee
Abstract: As a sequel to another paper of the authors on welding-induced initial deformations [1], this paper aimed to obtain a direct measurement database of welding-induced biaxial residual stresses in a full-scale steel stiffened plate structure and also to study the applicability of computational models to predict them. A full-scale steel stiffened plate structure in association with plate panels in bottom structures of an as-built containership carrying 1900 TEU was fabricated using exactly the same welding technology as used in today's shipbuilding industry. The X-ray diffraction method was employed to measure the biaxial residual stress distributions in the plating. In addition to simple formula estimations, computational models using the three-dimensional thermo-elastic-plastic finite element method were applied to predict the biaxial residual stress distributions. A comparison between full-scale measurements, numerical predictions and simple formula estimations was made. Details of the full-scale measurements are documented as they can be useful to validate the computational models formulated by other researchers.